Effect of surfactant concentration in sodium ascorbate on contact angle and tensile bond strength after bleaching - Yulianasari S; Pribadi Santosa; Tunjung Nugraheni (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Free radical residue due to intracoronal bleaching using 35% hydrogen peroxide (HP) can be removed with 35% sodium ascorbate (SA) combined with surfactants. This study aimed to determine the effect of surfactant concentration in SA 35% on the contact angle and tensile bond strength of composite resin after intracoronal bleaching with 35% HP. The contact angle was observed in 3 groups of 35% SA: group 1 (without surfactant); group 2 (with 0.2% surfactant); group 3 (with 0.4% surfactant). Each sample was dropped on a glass slide perpendicularly, then the image was taken at the fifth minute and contact angle value was obtained using ImageJ software. Tensile bond strength in this study used 21 premolars, which were cut and fixed with acrylic resin. 35% HP (0.01 ml) was applied to tooth surface for 5 days, then washed and dried. Specimens were divided into 3 groups, each of which was applied with 0.01 ml 35% SA without surfactant (group 1), 35% SA with 0.2% surfactant (group 2), and 35% SA with 0.4% surfactant (group 3) for 5 minutes, before they were washed and dried. All specimens were filled with composite resin, and incubated in artificial saliva for 7 days inside an incubator (37oC) before the specimens were tested with Universal Testing Machine (speed 0.5 mm/minute). ANOVA analysis showed the effect of surfactant concentration in 35% SA on the contact angle and tensile bond strength after intracoronal bleaching with 35% HP. In conclusion, 35% SA with 0.4% surfactant had a smaller contact angle and application of 35% SA with 0.4% surfactant after intracoronal bleaching with 35% HP had a greater tensile bond strength.